2020
DOI: 10.21203/rs.3.rs-23746/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in Alzheimer’s-related Tau biomarkers and a mediating effect of testosterone

Abstract: Women show greater pathological Tau biomarkers than men along the Alzheimer’s disease (AD) continuum, particularly among apolipoprotein ε-E4 (APOE4) carriers; however, the reason for this sex difference in unknown. Sex differences often indicate an underlying role of sex hormones. We examined whether testosterone levels might influence this sex difference and the modifying role of APOE4 status. Analyses included 172 participants (25 cognitively normal, 97 mild cognitive impairment, 50 AD participants) from the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…40-42). Several recent studies have also suggested a stronger relationship between ApoE4 genotype and CSF tau levels among women, especially in the presence of greater amyloid burden, 43-46 but the results have been mixed, 40,47 and overall, the literature is sparse. Despite the sizeable number of individuals who progressed from normal cognition to MCI symptom onset, this study may have been underpowered to detect significant 2-way and 3-way interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40-42). Several recent studies have also suggested a stronger relationship between ApoE4 genotype and CSF tau levels among women, especially in the presence of greater amyloid burden, 43-46 but the results have been mixed, 40,47 and overall, the literature is sparse. Despite the sizeable number of individuals who progressed from normal cognition to MCI symptom onset, this study may have been underpowered to detect significant 2-way and 3-way interactions.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42]. Several recent studies have also suggested a stronger relationship between ApoE4 genotype and CSF tau levels among women, especially in the presence of greater amyloid burden, [43][44][45][46] but the results have been mixed, 40,47 Elucidating the natural history of AD in its presymptomatic phases is essential for the design of clinical trials in which cognitively normal individuals would be enrolled, because such data provide information about those most likely to progress within specific periods. Of note, an analysis of placebo data from a large number of MCI clinical trials demonstrated that many subjects had limited progression over the trial time frame, making it difficult to determine whether the treatments were efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a strong sex‐specific association between APOE ε4 and AD has been reported in women, but only among those aged 65–75 years [53], which might suggest that the APOE ε4 effect on CSF tau levels in women is not present in EOAD. On the other hand, no differential effect of APOE ε4 has been found on tau‐PET retention [31], and testosterone levels might mediate the influence of APOE ε4 on CSF tau [54]. In contrast to CSF tau levels, higher CSF NfL levels among men with AD have been previously reported, and sex‐specific reference intervals have been proposed [15, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed a significant difference in Tau-2 levels between males and females (P = 0.001). Prior studies have shown that testosterone may have a neuroprotective effect against phospho-tau in Alzheimer’s patients, especially APOE4 carriers 32,32 . Some have also shown that estrogen interacts with tau to inhibit hyperphosphorylation and aggregation 34 .…”
Section: Discussionmentioning
confidence: 99%